Clinical malaria diagnosis in adults: the value of signs symptoms and antibodies (2004)
In the absence of microscopic examination, the high prevalence of asymptomatic malaria infections and the non-specific symptoms of the disease make clinical diagnosis difficult in highly endemic areas. Data from daily medical records 0f 111 adult volunteers obtained in a 13-month longitudinal survey were analysed using Pearson's correlation to investigate the relationship between parasitaernia and clinical symptoms and to determine the predictive strength of various clinical symptoms for malaria. Forty three percent of the subjects were blood smear positive at one or more times in the study. Parasite prevalence and clinical symptoms followed a seasonal distribution, being higher and occurring more often in the high transmission periods. High antibody responders to the circumsporozoite protein (CSP) showed lower parasite prevalence and fewer symptoms compared to the other responders. Malaria parasitaemia was significantly correlated with fever (p < 0.01). Fever, joint pain and headaches could be useful in endemic areas as symptom indicators of malaria for adults.